Engineering fibroblast with reprogramming and spheronization for bone defect repair - Yanjiao Li; Bin Jiang; Zhen Wu; Zhaoxia Ma; Lihua Qiu; Wen Cui; Yunhui Zhao; Jinghe Yan; Daiping Ma; Xingfei Wu; Shu Liang; Sitao Wang; et al. (Bioactive Materials)
Bone diseases profoundly affect patients, particularly the elderly, leading to severe health complications and disabilities. Osteoblasts play a crucial role in bone formation and are ideal candidates for treating bone diseases and engineering living materials. However, the stem and progenitor cells that give rise to osteoblasts, as well as osteoblasts themselves, exhibit dysfunction with aging. Although chemical reprogramming of fibroblasts into osteoblasts has been achieved, effective cell-based therapies or living materials have not been established in clinical practice. Here, we present a method to engineer fibroblasts through small molecule reprogramming and spheronization, achieving functional osteoblastic materials across all age groups. By primarily targeting the WNT signaling pathway and modularizing small molecules based on their effects on stage-specific genes, we optimized the temporal regulation of small molecules during reprogramming, acquiring a large number of healthy induced osteoblasts (iOBs). These iOBs with traits of functional native osteoblasts are ideal for forming transplantable tissue spheroids. As innovative living materials, the iOB spheroids (iOB-Sps) have demonstrated improved survival, significant self-bone formation, reduced ROS levels in the defect microenvironment, and accelerated endogenous osteogenesis and angiogenesis in vivo, promoting effective healing of bone defects. These material-free iOB-Sps function as self-scaffolding building blocks for biofunctional constructs, offering a promising avenue for clinical autologous bone defect repair, especially for the elderly.